A comprehensive review on the phytoconstituents and biological activities of Nyctanthes arbor-tristis L. - Ni Kadek Santi Maha Dewi, Nanang Fakhrudin, Subagus Wahyuono (Journal of Applied Pharmaceutical Science, 2022)
Nyctanthes arbor-tristis (NAT) is one of the Indonesian herbal medicines which belongs to the genus Nyctanthes and the Oleaceae family. Traditionally, NAT is used to reduce fever and pain and treat hemorrhoids, irregular menstruation, cough, and asthma. This review article aimed to examine the phytoconstituents and pharmacological activities of NAT from different plant parts. The literature search was conducted through PubMed and Google Scholar databases. Our literature study showed that NAT has various secondary metabolites, such as steroids, terpenes, flavonoids, phenol, iridoid glycosides, and alkaloids. These compounds are distributed in the leaves, seeds, flowers, and stem bark. Different chemical structures of secondary metabolites are present in each plant part, and each demonstrates distinct pharmacological activities. The most common activities found in the literature are antimicrobial, analgesic, antiinflammatory, antidiabetic, antioxidant, hepatoprotective, antitussive, and antimalarial activities. Although this plant offers a promising source for drug discovery, the pharmacological and phytochemical data are still limited. Further studies are needed to explore the potency of NAT as natural products benefiting human health.
Keywords: Herbal medicine, night flowering jasmine, pharmacology, secondary metabolite, traditional use